PENGARUH ADVERTISING & SALES PROMOTION MELALUI FACEBOOK ADS TERHADAP VOLUME PENJUALAN - Wa Ode Noni Indriani (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The era of the development of information technology has had a good impact on the promotion aspect. The latest research as of February 2022 states that 68.9 percent or 191.4 million people of the total Indonesian population are active pengguna of social media. One of the social media that is being loved is Facebook with 81.3% pengguna. Facebook is a social media that is considered potential to carry out advertising and sales promotion activities. This study uses an associative quantitative approach with a sample of 100 respondents who are business people who use facebook ads as a promotional medium. The instrument used in this study was a questionnaire. Data analysis used descriptive analysis and statistical data analysis, for hypothesis testing using correlation analysis, path analysis, R-Square, T-test, and Sobel test. The results showed that there was a significant direct influence between advertising and sales promotion on sales volume with a significance value of 0.001 < 0.05 (X1 to Z) and 0.003 < 0.05 (X2 to Z), as well as an indirect effect between advertising and sales promotion through Facebook ads on sales volume with a Sobel test value of 3.159 > 1.96 (X1 through Y to Z) and area and does not take into account other variables that influence sales volume.2.319 > 1.96 (X2 through Y to Z). This study only involves samples in the JABODETABEK